Vogt-Koyanagi-Harada Disease Exacerbation Associated with COVID-19 Vaccine - Begoña De Domingo; Miguel López; Maria Lopez-Valladares; Esperanza Ortegon-Aguilar; Bernardo Sopeña-Perez-Argüelles; Francisco Gonzalez (Cells, 2022)
We describe a case of Vogt-Koyanagi-Harada (VKH) disease exacerbation after COVID-19 vaccination. A 46-year-old woman presented with a bilateral granulomatous uveitis 2 days after the first dose of COVID-19 mRNA vaccine (Comirnaty, Pfizer-BioNTech), and was diagnosed with a complete Vogt-Koyanagi-Harada (VKH) disease 4 days after receiving the second dose of the vaccine. Three weeks before the first dose, she had been consulted for blurred vision and mild headaches. The case resolved with high dose intravenous corticosteroids, followed by oral prednisone. The close temporal relationship between the COVID-19 vaccine doses and the worsening of VKH symptoms strongly suggests COVID-19 vaccination as the trigger of its exacerbation.